ANALYSIS OF ACCOUNTING TREATMENT OF PRODUCTIVE ZAKAT DISTRIBUTION PRACTICES BASED ON PSAK 109 (CASE STUDY AT THE PIDIE JAYA ZAKAT AGENCY INSTITUTION) - Ikramul Hadi; Mudrikah; Muammar Khaddafi; Iswadi (PT. Radja Intercontinental Publishing, 2023)
This research aims to analyze the accounting treatment of productive zakat distribution practices and the suitability of implementing PSAK Syariah No. 109 at Baitul Mal, Pidie Jaya Regency with the concept of recognition, measurement, presentation and disclosure of PSAK Syariah No. 109. The type of this research is a case study. The research method used is descriptive analysis method. Data collection techniques in this research used interview and documentation methods. The results of the research show that the productive zakat distribution mechanism at Baitul Mal Pidie Jaya Regency in distributing productive zakat to mustahik still uses a grant contract, which means that the productive zakat funds given to mustahik are given free of charge and gradually they have started to use the qardhul hasan contract. The implications of productive zakat funds on the status of mustahik are not yet fully capable of changing mustahik into muzakki, the status of mustahik can only change into muktafi (people who are able to meet their own needs) and munfiq (people who give infaq). Apart from that, the research results show that the concept of recognition and measurement of zakat at Baitul Mal Pidie Jaya Regency is in accordance with PSAK Syariah No. 109. The concept of recognition and measurement of infaq/alms at Baitul Mal Pidie Jaya Regency is not fully in accordance with PSAK Syariah No. 109. The concept of presentation and disclosures at Baitul Mal Pidie Jaya Regency are in accordance with PSAK Syariah No. 109.